Reconfigurable network structure with tunable multiple deformation modes: Mechanical designs, theoretical predictions, and experimental demonstrations. (1st January 2023) - Zhang, Kai; Ji, Jinyu; Huang, Yixing; Song, Wei-Li; Wang, Hao; Wang, Li-Chen; Guo, Xiaogang; Fang, Daining
Abstract: Reconfigurable network structure with tunable multiple deformation modes exhibits promising applications in functional electromagnetic devices, frequency-reconfigurable antennas, flexible electronic devices, and robots with multiple motion modes due to its capability to realize multiple working characteristics in one device or system. In most previous studies on reconfigurable network structures with large deformation, researchers focus on tuning the deformation and mechanical properties for a specific deformation mode of the network structure. Therefore, designs for reconfigurable network structures to achieve multiple deformation modes and large deformation still remain a challenge. The inverse design of the reconfigurable network structure with desired mechanical responses under some specific external actuations is difficult due to the lack of theoretical models to describe the finite deformation of network structures actuated by external fields. This paper introduces a mechanical design strategy for the reconfigurable network structure to achieve a large deformation (over 45%) and multiple mechanical responses under the electrothermal actuation, including the uniform or non-uniform shrinkage and expansion, shearing, and bending deformation modes. Theoretical models for this reconfigurable network structure are developed to predict these unique mechanical responses and inversely design the reconfigurable network structure for the desired deformation modes in a facilitating method. The accuracy of the designed reconfigurable network structure is validated by the corresponding finite element analyses (FEAs) and experiments qualitatively and quantitatively. In accordance with these theoretical models, the deformed configuration and analytic solutions for some critical mechanical quantities, such as the electrothermally actuated effective strain for shrinkage, expansion and shearing deformation modes, and the bending angle for bending deformation modes, are obtained. The electrothermally actuated deformation of network structures can be tuned by the value of the normalized geometrical parameter d/t1 and the electrothermal actuation strategy. Furthermore, demonstrative experiments and FE simulations illustrate that multiple deformation modes can be achieved in the same network structure through the individual actuation strategy. This work provides guidelines from the aspects of theoretical predictions, FEAs, and experiments for future designs of the reconfigurable network structures to achieve desired mechanical responses.